Structural reliability analysis of steel plane frames with semi-rigid connections. - Agostini, Bruno Márcio (2018)
The design codes for structural design traditionally establish the adoption of partial safety factors to deal with uncertainties. These standards do not allow one to know the real probabilities of failure of a structure. What is needed, from a practical and scientific point of view, is a more consistent approach, based on reliability theory. This article addresses an initial attempt at determining the safety levels of structures based on advanced analysis and design with structural reliability theory. In this context, the authors consider the effects of the geometric nonlinearity and flexibility of connections in the reliability analysis, which aims at setting a certain displacement as the service limit state. For this purpose, a computer program was written called Structural Reliability Module. This program uses a First Order Reliability Method to analyse reliability. To carry out the structural analysis of steel structures, this study uses the program Computational System for Advanced Structural Analysis. Validating the Structural Reliability Module involved comparing the results from other authors with those generated by the program. Results for the structures under study indicate the efficiency of the implemented measures. Results suggest that, when a certain displacement is set as a service limit state, the reliability of the structures under analysis are only slightly influenced by geometric nonlinearity but considerably so by semi-rigid connections.